Temporal dynamics of the face familiarity effect: bootstrap analysis of single-subject event-related potential data - Alonso-Prieto, Esther; Pancaroglu, Raika; Dalrymple, Kirsten A.; Handy, Todd; Barton, Jason J. S.; Oruc, Ipek (Cognitive neuropsychology, 2015)
Prior event-related potential studies using group statistics within a priori selected time windows have yielded conflicting results about familiarity effects in face processing. Our goal was to evaluate the temporal dynamics of the familiarity effect at all time points at the single-subject level. Ten subjects were shown faces of anonymous people or celebrities. Individual results were analysed using a point-by-point bootstrap analysis. While familiarity effects were less consistent at later epochs, all subjects showed them between 130 and 195 ms in occipitotemporal electrodes. However, the relation between the time course of familiarity effects and the peak latency of the N170 was variable. We concluded that familiarity effects between 130 and 195 ms are robust and can be shown in single subjects. The variability of their relation to the timing of the N170 potential may lead to underestimation of familiarity effects in studies that use group-based statistics.